Similes in D.H. Lawrence’s “Sons and Lovers” - Matevosyan, Armine; Melkonyan, Anna (Armenian Folia Anglistika, 2009)
The article highlights the role of similes in D.H. Lawrence’s “Sons and Lovers”.Simile is an expressive means of poetic speech that helps readers form a more comprehensive picture of the characters and their inner world.D.H. Lawrence is among the writers of the psychological novel who masterfully use simile in its full power and capacity and bring emotionality to the text.